Properties of the circumgalactic medium in cosmic ray-dominated galaxy haloes. Issue 4 (26th June 2020) - Ji, Suoqing; Chan, T K; Hummels, Cameron B; Hopkins, Philip F; Stern, Jonathan; Kereš, Dušan; Quataert, Eliot; Faucher-Giguère, Claude-André; Murray, Norman
ABSTRACT: We investigate the impact of cosmic rays (CRs) on the circumgalactic medium (CGM) in FIRE-2 simulations, for ultra-faint dwarf through Milky Way (MW)-mass haloes hosting star-forming (SF) galaxies. Our CR treatment includes injection by supernovae, anisotropic streaming and diffusion along magnetic field lines, and collisional and streaming losses, with constant parallel diffusivity $κ \sim 3× 10^{29}\, \mathrm{cm^2\ s^{-1}}$ chosen to match γ-ray observations. With this, CRs become more important at larger halo masses and lower redshifts, and dominate the pressure in the CGM in MW-mass haloes at z ≲ 1–2. The gas in these 'CR-dominated' haloes differs significantly from runs without CRs: the gas is primarily cool (a few ${\sim}10^{4}\, $ K), and the cool phase is volume-filling and has a thermal pressure below that needed for virial or local thermal pressure balance. Ionization of the 'low' and 'mid' ions in this diffuse cool gas is dominated by photoionization, with O vi columns ${\gtrsim}10^{14.5}\, \mathrm{cm^{-2}}$ at distances ${\gtrsim}150\, kpc$ . CR and thermal gas pressure are locally anticorrelated, maintaining total pressure balance, and the CGM gas density profile is determined by the balance of CR pressure gradients and gravity. Neglecting CRs, the same haloes are primarily warm/hot ($T\gtrsim 10^{5}\, $ K) with thermal pressure balancing gravity, collisional ionization dominates, O vi columns are lower and Ne viii higher, and the cool phase is confined to dense filaments in local thermal pressure equilibrium with the hot phase.